Bacillus clausii and gut homeostasis: state of the art and future perspectives. (2nd August 2016) - Lopetuso, Loris R.; Scaldaferri, Franco; Franceschi, Francesco; Gasbarrini, Antonio
ABSTRACT: Introduction : The intestinal barrier is a complex system responsible for the host health. Many gastrointestinal and extra-intestinal diseases are associated to gut barrier disruption. An increasing interest on nutritional supplements and functional foods focused on the hypothesis that specific prebiotics and probiotics may modulate and interact with gut barrier, re-establishing gut homeostasis. Areas covered : The application of preparations containing B. clausii in the treatment or prevention of gut phisiology impairment has been largely supported in the last years and has driven its clinical applications. This review focuses on B. clausii clinical applications and speculates on the possible interactions among B. clausii, gut barrier and immune system and on the consequences of this interplay in modulating human health. Expert commentary : Its favorable effects have been linked to several properties, such as antimicrobial and immunomodulatory activity, regulation of cell growth and differentiation, cell-cell signaling, cell adhesion, signal transcription and transduction, production of vitamins and gut protection from genotoxic agents. In this scenario, future studies will need to better clarify its mechanisms of action and focus on the possible role of B. clausii in modulating gut immune system.